Empowering the youth through online social enterprise income generation: a study in Malaysia and USA - Ishak, Noormaizatul Akmar; Osman, Muhamad Zulkiflee; Syed Idrus, Syed Zulkarnain; Wan Ali, Wan Nor Ashiqin; Bahari, Azizan; Azahari, Nur Azila (2016)
As Malaysia’s economy becomes increasingly developed, the quality of its education improves along with income ranks. However, the issue of school dropouts is “a thorn in the flesh” that affects the rise in income and hence the quality of life in Malaysia.As such the dropouts need to be exposed to self-empowerment and systematic financial education in order to be independent and at the same time able to steer themselves away from the dangers of crime.Taking advantage of the current digital trend, most of the dropouts are familiar with the Information and Communication technology (ICT), the internet and mobile applications.This study recommends that for the next phase in their dealing with school dropouts, the Malaysian authorities should build a prototype of the business model of Social Enterprise that is successfully in operation in the United States. Nevertheless, some adaptation should be made in order to suit with the Malaysian context.In the final phase, the authorities could also work out spin-off businesses through provision of seed funds, including from interested private sectors, to these youths.